KONTRIBUSI KELINCAHAN DENGAN KEMAMPUAN DRIBBLING PEMAIN SEPAKBOLA SMA N 1 TEBING TINGGI - Aang Hadi Hendra K; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT This study at the start of a lack of ability dribbling soccer player SMAN 1 Tebing Tinggi. It is influenced by several factors, physical condition, one of them is a factor agility. The purpose of this study was to determine how big contribution to the agility of dribbling skills. Research is using the correlation method is to determine how much contribution to the agility of dribbling skills. A population of 21 people, then sampling with total sampling technique. To get the research data used Dodging run tests to measure agility and dribbling skills tests. Data were analyzed by Product Moment formula and to determine the contribution specified in the coefficient of determination (r²). Results obtained by analysis of the correlation coefficient r xy = 0.570> rtabel = 0433 (the research hypothesis is accepted) and testing the effect of correlations obtained t = 3,027> t table = 1.73 (significant) at the significant level α = 0:05. From the above results obtained value of determination (r²) = 0325, their contribution to the agility of 33%. It can be concluded that the hypothesis can be accepted.Keywords : agility, dribbling skills